The design and testing of a decision support tool for the evaluation of the reusability of glass wine bottles : a South African case study - Adriaanse, Frederik Gideon (Stellenbosch : Stellenbosch University, 2018)
Thesis (MCom)--Stellenbosch University, 2018.